Building a Sport Tourism Hub in the Heart of Central Java: A Comprehensive Analysis of Surya Yudha Park Banjarnegara Development - SUBARA, Ari; PRANOTO, Pranoto (Journal of Tourism Economics and Policy, 2025)
This study analyzes the potential for developing Surya Yudha Park Banjarnegara as a leading sports tourism destination in Central Java. This qualitative research was conducted for three months (January-March 2025) using in-depth interview methods, participatory observation, and documentation studies of 11 key informants. The results of the study indicate that Surya Yudha Park has enormous strategic potential to develop into a sports tourism hub thanks to its strategic geographical position as the "heart of Central Java", complete sports facilities (international standard futsal field, sports swimming pool, fitness center, and indoor tennis court), and government policy support through the "10 New Bali" program. However, there are significant challenges in the form of limited expertise in sports facility management, HR competency gaps, an unintegrated management system, limited accessibility, and competition with metropolitan destinations. Recommended quality improvement strategies include: adoption of a three-phase development approach, organizational restructuring with the formation of a Sport Tourism Division, integration of a smart facility management system, formation of a Sport Tourism consortium, and revenue diversification. The implementation of this strategy is expected to position Surya Yudha Park as a leading sports tourism destination that contributes to local economic development and sustainable tourism.